Implementation of Game Based Learning Model Using Tangkas Board Media to Improve Learning Outcomes of Third Grade Students at State Elementary School 25 Pekanbaru - Amandha Pranita; Guslinda; Tri Heni Endang Pamiluwati; Meyda Putri Alfitra (Jurnal Kiprah Pendidikan, 2025)
This study aims to improve the learning outcomes of third-grade students at SD Negeri 25 Pekanbaru on the material of Rights and Obligations through the application of the Game Based Learning model using the Papan Tangkas media. This study is a Classroom Action Research (CAR) carried out in 2 cycles, which refers to the Kemmis and McTaggart model. Each cycle consists of Planning, Action, Observation, and Reflection. The data required in this study are quantitative data in the form of student learning outcomes (pretest, posttest Cycle I, and posttest Cycle II) and the percentage of learning completion. While qualitative data is obtained through observations based on student activities and participation in the learning process. The data collection instruments used are learning outcome tests and observation sheets to observe student activities. The results of the study show that the application of the Game Based Learning model using the Papan Tangkas media can improve student learning outcomes. The average student score increased from 69.45 in the pre-cycle to 81.54 in Cycle I and 87.09 in Cycle II. This shows that the Game Based Learning model is effective in improving students' learning outcomes and their involvement in learning.